2020
DOI: 10.3389/fonc.2020.01621
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Radiomics of B-Mode Ultrasonography and Shear-Wave Elastography: Improved Performance in Breast Mass Classification

Abstract: Objective Shear-wave elastography (SWE) can improve the diagnostic specificity of the B-model ultrasonography (US) in breast cancer. However, whether deep learning-based radiomics signatures based on the B-mode US (B-US-RS) or SWE (SWE-RS) could further improve the diagnostic performance remains to be investigated. We aimed to develop the B-US-RS and SWE-RS and determine their performances in classifying breast masses. Materials and Methods This retrospective study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Quantitative SWE parameters used alone have been able to classify breast lesions with a specificity of 86% and a sensitivity of 84% (27). Our results also agree with a previous study that found Emax to be the best-performing parameter in classifying breast lesions, achieving the highest AUC of 0.90 (95% CI, 0.77-1.00) (15). Similarly, the integration of SWE and B-US has been shown to improve diagnostic efficacy in breast cancer screening, particularly in specificity (28).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Quantitative SWE parameters used alone have been able to classify breast lesions with a specificity of 86% and a sensitivity of 84% (27). Our results also agree with a previous study that found Emax to be the best-performing parameter in classifying breast lesions, achieving the highest AUC of 0.90 (95% CI, 0.77-1.00) (15). Similarly, the integration of SWE and B-US has been shown to improve diagnostic efficacy in breast cancer screening, particularly in specificity (28).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, there were 77 patients enrolled in the external validation cohort 1 and 55 in the external validation cohort 2, making a total of 259 patients in our study. Compared to previously published studies, Zhang et al conducted a retrospective study of 291 women from 2 centers to compare the diagnostic performance between B-US and SWE in classifying breast masses (15). Patients were divided into a training cohort (n=198), an independent validation cohort (n=65), and an external test cohort (n=28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, seven such features achieved an AUC of 0.917 for the identification of breast malignancies. A more recent study by Zhang X. et al compared deep-learning based radiomics scores acquired from B-mode US and shear-wave elastography (SWE) with the results of the BI-RADS assessment and quantitative SWE parameters and found a significant increase in the diagnostic performance by using radiomics scores, reaching an AUC of 1 for both [75]. On the preclinical level, Theek et al performed a radiomics analysis of CEUS data from different mouse tumor models, achieving correct classifications in 82.1 % of cases [76].…”
Section: Lesion Characterizationmentioning
confidence: 99%
“…The performance of the brain metastases prediction model (under 10-fold cross-validation mode) The confusion matrix of the Naïve Bayes brain metastases prediction model (the percentages were calculated based on actual value) The triple-negative breast cancer brain metastases risk-prediction nomogram (based on whole cohort data and Naïve Bayes method). treatment response prediction(7,(21)(22)(23)(24)(25). Braman et al used peritumoral radiomics characteristics to predict the tumor microenvironmental status and treatment response of HER-2 positive breast cancer(26).…”
mentioning
confidence: 99%